The Effectiveness of Relaxation and Imagination in the Suggestopedia Method on Students' Maharah al-Kalam at the Elementary School Level - Laili Maulidiana; Eka Najilatul Lailatun Nisa; Winda Khoirun Nisak (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Nahdlatul Ulama Blitar, 2026)
This study aims to analyze the effectiveness of relaxation and imagination techniques within the Suggestopedia method in improving the maharah al-kalam (Arabic speaking skills) of elementary school students. A quasi-experimental design with a nonequivalent control group was employed. The research subjects consisted of 25 students from Class IV-A of SD Al Islah Tulungagung as the control group and 24 students from Class IV-B as the experimental group. The control group received conventional Arabic language instruction through lecture, question-and-answer, and vocabulary memorization, while the experimental group received Suggestopedia-based learning that incorporated relaxation, positive suggestion, instrumental music, guided imagination, and conversational practice. Data were collected through a maharah al-kalam test administered before and after the treatment, evaluating pronunciation, fluency, vocabulary accuracy, and the ability to convey ideas. Data analysis was conducted using an independent sample t-test and the N-Gain formula. The results indicated that the post-test mean score of the experimental group (82.46) was significantly higher than that of the control group (71.28). The t-test revealed a statistically significant difference between the two groups (p = 0.001 < 0.05). Furthermore, the experimental group achieved an N-Gain value of 0.68, compared to 0.39 in the control group. These findings demonstrate that the application of relaxation and imagination within the Suggestopedia method is effective in enhancing students’ maharah al-kalam. This method has the potential to serve as a more engaging alternative for Arabic language learning, fostering students’ self-confidence and encouraging active participation in communication.